RANCANG BANGUN PEMBUATAN BANGKU DAN MEJA TAMAN - Mulya, Encep; Maryoni; Fidril Marta (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2021)
Environmental comfort is one of the important aspects in the world of education, one of which is the manufacture of park benches and chairs. Making garden benches and chairs is made by designing a picture of the product you want to make, then selecting a suitable material, then taking measurements, cutting the material. Then the material is assembled and welded. The production cost used in making this product is Rp. 1.072.000 and has a selling price of Rp. 1.400.000.